Resolution of Light Transmission via Arduino-Based STEM Education Material - Erol, Mustafa; Demir, Yasemen (Jurnal Pendidikan Fisika Indonesia, 2024)
This study reports a basic experimental procedure to measure light transmission through some transparent materials through Arduino microprocessors. The basic experimental material is made up of materials used daily by elementary students, and the procedure is very simple and can surely be employed for teaching activities as STEM education material. The STEM material particularly focuses on transmission rates as a function of the thickness of the material. The absorption rates are experimentally measured using a specially designed box with two separated parts with a small window and an Arduino Uno microprocessor connected to an appropriate light detector structured as STEM education material. The experimental resolutions are managed for two materials, namely blue acetate and red acetate, with different thicknesses. The absorption coefficients are found to be 2.89 mm-1 for blue acetate and 1.54 mm-1 for red acetate. This work offers inexpensive teaching material that can create an education environment where students can feel dynamic and encompass the acquisitions of Science, Technology, Engineering, and Mathematics.